Autoantibodies against tumor‐associated antigens combined with microRNAs in detecting esophageal squamous cell carcinoma. (19th December 2019) - Sun, Guiying; Ye, Hua; Wang, Xiao; Li, Tiandong; Jiang, Di; Qiu, Cuipeng; Dai, Liping; Shi, Jianxiang; Wang, Kaijuan; Song, Chunhua; Wang, Peng; Zhang, Jianying
Abstract: Esophageal carcinoma (EC) is a common malignant disease worldwide, especially in China. There is currently no specific blood test for detecting EC. Autoantibodies against tumor‐associated antigens (TAAbs) and microRNAs (miRNAs) are promising markers for cancer diagnosis and this study focuses on combining TAAbs and miRNAs to evaluate the diagnostic value in esophageal squamous cell carcinoma (ESCC). The expression levels of seven TAAbs and five microRNAs in plasmas from 125 patients diagnosed with ESCC and 125 healthy individuals were detected by enzyme‐linked immunosorbent assay (ELISA) and reverse transcription quantitative‐polymerase chain reaction (RT‐qPCR), respectively. The receiver operating characteristic (ROC) analysis was applied to estimate the diagnostic value of these markers for distinguishing ESCC patients from normal individuals. Logistic regression analysis was performed to generate prediction model and calculate the probability of individuals being diagnosed with ESCC. Three panels were established including four TAAbs, three miRNAs, and three TAAbs combined with three miRNAs. The panel consisting of three TAAbs (HCCR, C‐myc, and MDM2) and three miRNAs (miR‐21, miR‐223, and miR‐375) attained great diagnostic value for ESCC, with an area under the receiver operating characteristic curve (AUC) of 0.89 (95% CI: 0.85‐0.93) with the sensitivity of 69%, the specificity of 90%, the PPV of 83%, the NPV of 79%, and the coincidence rate of 81%. The optimal panel of six‐member markers was able to effectively discriminate the patients with ESCC from normal individuals, especially for early esophageal squamous cell carcinoma. Abstract : The panel consisting of three TAAbs (HCCR, C‐myc, and MDM2) and three miRNAs (miR‐21, miR‐223, and miR‐375) attained great diagnostic value for ESCC, with an area under the receiver operating characteristic curve (AUC) of 0.89 (95% CI: 0.85‐0.93) with the sensitivity of 69%, specificity of 90%, and the coincidence rate of 81%. Our results reveal that using the combination of microRNAs and TAAbs may aid to diagnose ESCC, especially for ESCC at the early stage.